The Students’ Perception Toward the Implementation of Role Play Technique in Online-Based Speaking Learning - Noor Amartya Rusgiani (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2022)
The paper entitled “The Students’ Perception Toward the Implementation of Role Play Technique in Online-Based Speaking Learning” was purposed to describe students' perception of online-based speaking learning using role play techniques. This research was conducted at SMKN 1 Cibinong class XI TOI 1. This research used descriptive qualitative research guided by the research question